2018
DOI: 10.1016/j.schres.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein (TSPO) and stress cascades in mouse models of psychosis with inflammatory disturbances

Abstract: Changes in inflammatory cascades have been implicated in the underlying pathophysiology of psychosis. Translocator protein 18 kDa (TSPO) has been used to assess neuroinflammatory processes in psychotic disorders. Nonetheless, it is unclear whether TSPO, a mitochondrial protein, can be interpreted as a general marker for inflammation in diseases involving psychosis. To address this question, we investigated TSPO signaling in representative mouse models for psychosis with inflammatory disturbances. The maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
(96 reference statements)
2
7
0
Order By: Relevance
“…In line with previous results [41,56], we found a region-dependent increase of [18F]-GE180 uptake in cuprizone-treated mice (Figure 2A). A visual interpretation of the TSPO μPET scans indicated increased tracer uptake, particularly in the corpus callosum, caudoputamen, thalamus and cortex regions (Figure 2B).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In line with previous results [41,56], we found a region-dependent increase of [18F]-GE180 uptake in cuprizone-treated mice (Figure 2A). A visual interpretation of the TSPO μPET scans indicated increased tracer uptake, particularly in the corpus callosum, caudoputamen, thalamus and cortex regions (Figure 2B).…”
Section: Resultssupporting
confidence: 93%
“…In this study, we were able to demonstrate that cuprizone-induced demyelination is paralleled by an increase in TSPO radioligand (18F)-GE180 uptake. Comparably, increased uptake of different TSPO ligands, namely, [ 3 H]-(R)-PK11195 [58,68], (123I)-CLINDE [41], and (125I)iodo-DPA-713 [56], has been shown in the cuprizone model. It was suggested that, in the cuprizone model, the observed increase in [3H]-R-PK11195 binding is a result of an increase in the apparent number of binding sites rather than a change in receptor binding affinity [58].…”
Section: Discussionmentioning
confidence: 99%
“…the HC and thalamus in vivo . Our results add more detailed regional information to previous studies that have shown increased TSPO binding using ex vivo autoradiography in the CPZ model during demyelination and remyelination phases 49, 52-54.…”
Section: Discussionsupporting
confidence: 73%
“…However while TSPO-based PET imaging signals have often been considered to support neuroinflammatory theories of disease [ 9 11 ], it appears difficult, if not impossible, to define the precise pathophysiological meanings and cellular sources of altered TSPO binding in such studies. In some pathological conditions, increased TSPO expression may primarily reflect ongoing inflammatory processes [ 58 60 ], whereas in others it may signify anomalies in cellular metabolism and energy production [ 17 ], oxidative stress [ 61 ], and/or neuronal activity (present findings). The ambiguity of conceiving TSPO simply as a biomarker of neuroinflammation or microglial activation warrants caution, and supports the urgent development of novel approaches for assessing changes in inflammatory states in the brain [ 4 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 60%